INTELLECTUAL CAPITAL DAN KINERJA KEUANGAN PERBANKAN (PENDEKATAN DINAMIS PADA PANEL DATA) - Ghozali Maski (University of Merdeka Malang, 2013)
The performance of economic entities had been a research matter even in the ancient world. The genius humanhad been recognized as a vehicle for certain valuable capabilities and as the critic of transforming processes.But it had not been considered as an intellectual capitalizator or intellectual asset. The field for intellectualcapital and the related philosophy of knowledge management had risen recently to an interesting researchobject world wide. Value Added Intellectual Coefficient (VAIC) method and Rate of Growth IntellectualCapital (ROGIC) were applied in order to analyze the dynamic effect of Indonesia commercial banks for thefinancial period 2005 quarter 1 until 2008 quarter 4. It focused on banking financial performance both forcurrent period and the future. The research method was quantitative analysis and the sample were 22 banks byusing purposive sampling method. The method of estimation was dynamic model on panel data.The result ofthe study was all banks had relatively smaller capital employed efficiency than human and structural efficiencies.The long term effect had greater impact for return on asset and solvency ratio compared to the short termone. Average response time required for adjustment of return on asset was faster then solvency ratio.